Chinese Surplus Biopolitical Aesthetics and the Medically Commodified Body - Heinrich, Ari Larissa (Duke University Press, 2018)
In CHINESE SURPLUS Ari Heinrich dissects the figure of the medically or artistically commodified body in Chinese culture and popular science. Providing a history of how bodies have been thought and seen to mirror the nation, Heinrich charts the trajectory from an imperial idea of the body as a machine with interchangeable parts to current representations in which the parts are worth more than the whole and may be harvested at will--what he calls a diasporic form of the body. In seeing the body this way Heinrich makes clear his case for a new method he calls biopolitical aesthetics, one that uses the tools of literary and visual culture analysis to restore agency to aesthetics in the production of meaning in life during contemporary biopolitical times.